Functional Outcome of Calcaneal Fractures Treated by Various Methods - Vatsal Vishnu; Patel, Ishani; Modi, Dhaval R.; Panchal, Naitik; Bhavsar, Nishant; Joshi, Arpit (Nigerian Journal of Orthopaedics and Trauma, 2019)
Introduction: Calcaneal fractures make up about 2% of all fractures. They account for 60% of major tarsal injuries. Anatomic restoration of the three‑dimensional anatomy of the calcaneum and restoration of weight‑bearing function is the goal of surgical management of calcaneal fractures. Over the years, various techniques have been developed to accomplish this goal. All these techniques have certain steps in common including disimpaction of the fragments, reduction of the displaced fragments either manually or percutaneously and protection of reduction with plaster pins and plaster, external fixation and open reduction and internal fixation. Materials and Methods: This is a retrospective study of 41 patients (50 fractures) with calcaneum fractures from 15 to 60 years of age, managed either conservatively or operated at our institution between 2012 and 2017, with regular detailed clinical and radiological follow‑up for minimum of 6 months. Results: In this series, we have used American Orthopaedic Foot and Ankle Society score for assessment of our result. Ninety‑three per cent fractures had good to excellent result in non‑operative group and 77% fracture had good to excellent result in the operative group. In intra‑articular fractures with joint depression pattern, 9 (69%) of the percutaneously fixed fractures had good to excellent results and 8 (66%) of the Open reduction and internal fixation (ORIF) group had good to excellent results. Eight (33%) with fair result had persistent heel widening and pain. One patient had loss of reduction, but all of them have returned to their original occupation. In intra‑articular fractures with Tongue type fracture, all 7 (100%) fractures had good to excellent results, whether they were fixed percutaneously or via open fixation. Conclusion: In this retrospective study, we observe that there was no significant difference noted, with respect to the functional outcome, between the operated and non‑operated group.